2021
DOI: 10.31235/osf.io/j9f3p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights towards cultural aspects and related impacts of Lesson Study practices: a systematic review

Abstract: Lesson Study (LS) is a professional development model that Japanese teachers have been utilizing for over a century. Although several scholars have proclaimed the benefits of adopting LS in international educational systems, it is still unclear how LS has been used and how it should be implemented in cultures beyond Japan. In order to shed light on the theme, an International Systematic Literature Review was conducted aiming to (1) identify specific features of LS practices as they are developed in different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(63 reference statements)
1
2
0
Order By: Relevance
“…It is noted that some studies investigated more than one subject. This result corroborates previous studies that identified that LS was most investigated in the field of mathematics education (GÜLHAN, 2021) followed by science (FLUMINHAN;SCHLÜNZEN;SCHLÜNZEN JUNIOR, 2021). Surprisingly, one study did not make it clear which subject area the LS approach involved.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is noted that some studies investigated more than one subject. This result corroborates previous studies that identified that LS was most investigated in the field of mathematics education (GÜLHAN, 2021) followed by science (FLUMINHAN;SCHLÜNZEN;SCHLÜNZEN JUNIOR, 2021). Surprisingly, one study did not make it clear which subject area the LS approach involved.…”
Section: Resultssupporting
confidence: 92%
“…In a systematic review carried out to investigate how the Lesson Study is implemented in Turkey, Gülhan (2021) identified that time to meet the teachers emerged as one of the difficulties for the development of LS. Along the same line, previous studies pointed to the necessity of investing resources in order to enable teachers to participate in the LS activities (TAKAHASHI;McDOUGAL, 2016;FLUMINHAN;SCHLÜNZEN;SCHLÜNZEN JUNIOR, 2021).…”
Section: Resultsmentioning
confidence: 94%
“…These include, for example, "migrants, refugees or students with disabilities, as well as others that do not belong in a particular group that is receiving special attention" (Messiou & Ainscow, 2020, p. 6), such as the ones that are very quiet or who present challenging behaviour. Whilst LS is rooted in the teachers´ perspective (Lewis et al, 2006;Fluminhan et al, 2021), the Inclusion Inquiry brings students´ engagements, views and contribution as central features to facilitate teachers´ development and improve their capacity to respond to diversity.…”
Section: Used a Designmentioning
confidence: 99%